Spiritual Care Readiness Among Newly Graduated Muslim Nurses: A Qualitative Approach - Dwi Setiowati; Hasani Ahmad Said (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2024)
Holistic nursing includes spiritual care, which benefits nurses' spiritual health and patients' healing. However, despite integrating Islamic spirituality into the nursing curriculum, there is a gap between previous research findings and feedback from student practice fields regarding the suboptimal spiritual care provided by UIN Syarif Hidayatullah nursing students. This study aims to explore the experiences of newly graduated Muslim nurses in terms of readiness for spiritual care. The study used a qualitative approach involving fourteen informants, including eight newly graduated nurses. Thematic analysis was conducted through transcription, coding, and theme formation. Seven themes were identified: (1) perceptions of spiritual care; (2) readiness and ability (mental, physical, psychological, social, spiritual); (3) experiences; (4) benefits of spiritual care; (5) success and hindrance factors; (6) efforts to improve spiritual care; and (7) the role of nursing education. There is a need for habituation in nursing education before graduation and the enhancement of spiritual care among newly graduated Muslim nurses to improve reflection in nursing care.